Assessment of attributes for choosing a dental center in Trujillo, Peru: patients versus dentists - Karem Maytee Carranza-Fernández; Ángel Steven Asmat-Abanto; Rosita Elena Espejo-Carrera (Universidad de Concepción., 2024)
Objective: To determine the difference between patients and dentists regarding the assessment of attributes for choosing a dental center in Trujillo, Peru. Materials and Methods: A comparative cross-sectional observational study was conducted involving a sample of 162 dentists and 162 patients from the Trujillo province in Peru. The data was collected through a virtual questionnaire, validated by experts, and assessed for reliability. Statistical analysis was performed using the U-Mann Whitney and Spearman correlation tests, with a significance level set at 5%. Results: Patients, in comparison to dentists, demonstrated a greater preference for selecting a dental center where the practitioner is a recognized specialist (p<0.001). Similarly, patients showed a preference for centers offering expedited appointments, advanced technology, and equipment, providing affordable and flexible payment options, free consultations, and having convenient parking and comfortable facilities (p<0.05). Conversely, dentists perceived that the most valued attribute by patients is the recommendation of the dentist (p=0.031). Conclusions: When choosing a dental center, patients primarily value attributes related to both the professional responsible for care and administrative management. Conversely, dentists consider the main factor influencing a patient's choice of dental center to be recommendations of the dentist. Valoración de los atributos para la elección de un centro odontológico en Trujillo, Perú: pacientes versus odontólogos